The Effect of Instrument Assisted Soft Tissue Mobilization on Improving Joint Range of Motion in Active Individuals: A Critically Appraised Topic - Cole Dearing; Andrea Cripps; Jenny Toonstra (Bowling Green State University, 2023)
In all activities that require physical movement, whether in athletics or in other daily tasks, it is important for joints to have adequate range of motion and flexibility. Soft tissue restrictions are very common pathologies in healthcare. Although a decrease in myofascial range of motion can arise from a variety of reasons such as biomechanical deformities, autoimmune diseases, or age, it is often caused by overtraining or musculoskeletal injuries in active populations. Instrument assisted soft tissue mobilization techniques are gaining popularity to assist in treating various soft tissue injuries and musculoskeletal pathologies. The belief is that by applying a stimulus to the soft tissue around a joint, it will increase the number of fibroblasts, through localized inflammation, and result in a realignment of collagen fibers2. While some studies have shown positive outcomes of instrument assisted soft tissue mobilization (IASTM), there has been limited evidence to determine the efficacy of this modality in improving joint range of motion (ROM).